2012
DOI: 10.1002/ajmg.a.35346
|View full text |Cite
|
Sign up to set email alerts
|

The face signature of fibrodysplasia ossificans progressiva

Abstract: Fibrodysplasia Ossificans Progressiva (FOP) causes extensive heterotopic bone formation due to heterozygous mutations in the glycine-serine activation domain of ACVR1 (ALK2), a bone morphogenetic protein type I receptor. Anecdotal observations of facial similarity have been made by clinicians and parents, but no objective quantitative analysis of the faces of FOP patients has ever been undertaken. We delineated the common facial characteristics of 55 individuals with molecularly confirmed FOP by analysing thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…In addition, many FOP patients have a small mandible. Variably dysmorphic facial features in the regions of midface and jaw suggested by Hammond et al [2012] are likely related to the canonical ACVR1 mutation and not described in patients with other mutations so far. Ectodermal features have been described in patients with other mutations too.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many FOP patients have a small mandible. Variably dysmorphic facial features in the regions of midface and jaw suggested by Hammond et al [2012] are likely related to the canonical ACVR1 mutation and not described in patients with other mutations so far. Ectodermal features have been described in patients with other mutations too.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…Some patients are reported with slow hair growth, which was also a feature occurring in the second or third decade of life. Hammond et al [2012] suggested that FOP patients often have longer, narrower faces than age-sex matched controls -males more so than females. In addition, many FOP patients have a small mandible.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…Signature graphs have been successfully used recently to link extreme facial dysmorphism in patients with epilepsy to novel micro-deletions and duplications 17,18 and rare conditions such as fibrodysplasia ossificans progressiva. 19 Face-brain shape correlation studies in mouse models have also benefitted from signature graph techniques. 20 Further technical details are provided as supplementary information and elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…20,30 The agreement of clinical categorization (Table 1) and classification using DSM representation of face shape was estimated from 20 random 90% to 10% training-unseen test pairs of subject subsets (stratified with respect to affected or unaffected status) by using receiver operating characteristic (ROC) curve analysis. To analyze the faces of those who were HE, we introduced signature graph [28][29][30] cluster analysis. Sequences of 35 contiguously aged control faces generated age-matched means for comparison and normalization.…”
Section: Face Analysismentioning
confidence: 99%
“…27 In this study of South African children, we used face shape to induce classification schemes and tested agreement with clinical FASD categorization. The more heterogeneous phenotype of HE forced us to introduce a clustering technique, 28 signature graph analysis, 29,30 which normalizes face shape and links individuals with similar facial dysmorphism. Signature graph analysis identified half of our HE group as having facial dysmorphism that was more FAS-like than control-like.…”
mentioning
confidence: 99%